2019
DOI: 10.3122/jabfm.2019.06.190016
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Ambulatory Patient Portal for Advance Care Planning Engagement

Abstract: Background: Primary care clinics need sustainable, population-based approaches to engage patients in advance care planning (ACP). Patient portal-based ACP tools may provide an option for patient engagement. Objective: To increase ACP outcomes by engaging older adults through portal-based ACP tools, including an electronic Medical Durable Power of Attorney (MDPOA) form. Methods: Geriatric clinic pilot of a multi-modal population-based outreach strategy for portal-based ACP tools. Outreach was to patients (n ‫؍‬… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Creating comprehensive and multidisciplinary care plans Care plans described by the included sources all focused on addressing patients’ goals of care, specifically goals of care nearing end of life. Eight studies incorporated ACP, 28 , 31 , 32 , 34 , 35 , 43 , 44 , 48 with one using an EHR ACP interface to allow for standardized planning. 44 Sources also focused on providing home-based care, featuring home assessments and interdisciplinary care home visits.…”
Section: Resultsmentioning
confidence: 99%
“…Creating comprehensive and multidisciplinary care plans Care plans described by the included sources all focused on addressing patients’ goals of care, specifically goals of care nearing end of life. Eight studies incorporated ACP, 28 , 31 , 32 , 34 , 35 , 43 , 44 , 48 with one using an EHR ACP interface to allow for standardized planning. 44 Sources also focused on providing home-based care, featuring home assessments and interdisciplinary care home visits.…”
Section: Resultsmentioning
confidence: 99%
“…We identified two tools (PatientSite and MyChart) that use a guided, patient-centered questionnaire to enable the completion of an advance directive [ 24 , 33 , 34 ]. Although most of the tools allow users to complete and submit an advance directive that directly integrates into the electronic health record [ 22 , 23 , 35 , 36 ], we identified one tool based on My Health Manager (a Kaiser Permanente portal built through Epic software) that links users to an external website to complete the advance directive [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 illustrates these findings in detail. Portal use was most often measured by the mean number of log-ins and duration in minutes [ 40 , 41 , 47 ], number of registered users [ 45 ], features accessed [ 38 , 40 , 41 , 47 ], or completed activities such as completing an AD or other ACP-related documentation [ 22 , 24 , 33 - 36 ] or inputting a daily goal [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Brungardt et al 11 reported on improving Advance-Care Planning (ACP) outcomes by engaging older adults through portal-based tools, including an electronic Medical Durable Power of Attorney form. Brief motivational messages about ACP via a patient portal were initiated, and if not read within 2 weeks, a mailed postcard reminder was sent.…”
Section: End-of-life Care and Advance-care Planningmentioning
confidence: 99%